Terms of Reference for a Desktop Study on Water Demand Management for an Industrial Area in Malaysia - Mar Iman, Abdul Hamid (2008)

(untitled)
A brief draft proposal of a study on water demand for National Hydrological Research Institute of Malaysia (NAHRIM).